Computation of maximum power point tracking of PV module using modified Newton Raphson technique - Siddhartha Behera; Manoj kumar Sahu; Twinkle Hazra; Rabindra Behera; Sunila Kumar Swain; Itishree Sahu; Sritam Parida; Sarat Kumar Swain (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The maximum power point tracking (MPPT) has been a popular terminology among those researchers who deal with one of the most available renewable energy resources called solar power. Many researchers have evolved and proposed a lot of techniques for tracking maximum power. But each technique has its pros and cons. Some techniques suffer from complexity as far as implementation is concerned, whereas other techniques lack accuracy. In current research work, it has been investigated the MPPT using Newton Raphson (NR) method, which has not yet received a good attention by researchers. After observing its limitation, this method is modified (i.e., abbreviated as modified Newton Raphson method (MNRM)) to make it suitable for extracting the maximum power from PV module. The feasibility and precision of this method depends upon accurate measurement of temperature and irradiation. By using MNRM, the presumption of initial value is close to the voltage corresponding to maximum power, so it leads faster converging to solution through a few rounds of iterations. In order to validate it, a MATLAB/Simulink model is developed and simulated. The proposed method is incorporated in PV module-fed buck converter so as to explore superior performance.